UNSUR-UNSUR DALAM PROSES PENDIDIKAN - Abdul Wahab Syakhrani; Nadia Alwiani; Nor Khalifah (ADIBA : JOURNAL OF EDUCATION, 2025)
This article explains the various important elements that shape and determine the success of an educational process. Education is understood as a system that involves dynamic interactions between educators, learners, educational objectives, learning materials, methods, infrastructure, and the environment as supporting factors. These elements are systematically interconnected to achieve the desired transformation of knowledge, skills, and values. Educators act as facilitators and motivators, while learners become active subjects in the learning process. Educational objectives provide clear direction for learning outcomes, while materials and methods are the operational means of achieving these objectives. The learning environment, both physical and social, provides a context that reinforces the effectiveness of the educational process. By understanding the interrelationship between each element, the educational process can be designed in a more systematic, efficient, and results-oriented manner.